Rewriting Representations of the Foreign: the Ireland of Finnish Realist Drama - Aaltonen, Sirkku (TTR, 1996)
AbstractRewriting Representations of the Foreign : the Ireland of Finnish Realist Drama — In this article, the author discusses what happens to culture-specific elements in the translation of realist drama. Following the polysystem approach, the hypothesis is that translation involves acculturation, or manipulation, even though realism as a style of presentation professes to be "lifelike." Which elements are acculturated, and how, is linked to the awareness assumed on the part of the audience of the cultural and generic conventions as well as of the dramatic function of the culture-specificelements in characterizationand the construction of plot, theme and atmosphere. Taking eight Irish plays rewritten into Finnish, the author concludes that they must be seen as products of the Finnish, not the Irish, theatrical system.